Synthesis and characterization of low-carbon cementitious materials from suspended calcined coal gangue - Jiu, Shaowu; Wang, Mingming; Chen, Yanxin; Chen, Jingyi; Gao, Qianwen (Frontiers in Materials, 2022)
Coal gangue is used to replace cement clinker to prepare cementitious material via activation techniques. Thus, the solid waste can be effectively disposed, and the carbon emission from cement production processes can be significantly reduced. In this paper, the product transformation, reaction mechanism, and thermal activation kinetics of coal gangue were analyzed by X-ray diffraction, thermal analysis, infrared analysis, and scanning electron microscopy. We employed a suspension calcination process to prepare high-activity metakaolin. A cementitious material was prepared from the metakaolin and cement, and the mechanical properties and hydration products were analyzed. The results show that metakaolin was formed by the dehydroxylation of kaolinite in the coal gangue during calcination, and the reaction was based on the Z–L–T three-dimensional diffusion mechanism with an activation energy of 190.2 kJ/mol. Metakaolin with dissolution rates of 69.5%–76.3% and 44.5%–52.3% of activated alumina and silica, respectively, were synthesized by calcining the coal gangue at 750ºC–850ºC for approximately 5 s via suspension calcination. The prepared cementitious material showed 28-d compressive strength of 57.5–61.5 MPa and an activity index of 114%–135%. The cementitious material participated in the hydration of cement and formed a structurally dense hardened body, which resulted in a high replacement volume and high strength of the specimens. The preparation of low-carbon cementitious materials by activating gangue via suspension calcination provides a basis for gangue utilization and reduction of carbon emissions during cement production.